PENGEMBANGAN MODEL PERMAINAN PASS POINT BASKETBALL UNTUK MENINGKATKAN KEMAMPUAN PASSING PADA SISWA KELAS X SMA NEGERI 1 SUBAH (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to develop and produce products in the form of model learning through games pass pointbasketball for student pass class X High School in penjasorkes learning .The method of this study is research onthe development , which refers to model the expansion of R & D in Sugiyono was modified , namely: (1) thepotential and problems, (2) pengumplan data, (3) product design (as the games pass point Basketball ), (4)design validation, (5) revisions design, (6) ui try small scale products (14 students) , (7) revision of the product,(8) large scale trials (35 students), (9) revision product, (10) products end . Data in the form of evaluation of thequality of the products , suggestions for improvement of the product, and the result of filling the questionnaireby the students and assisted in a survey observations by teachers penjasorkes appraisement SMA N 1 Subah .Data analysis techniques used are descriptive percentage to reveal aspects of psychomotor, cognitive andaffective student after using the product.From the results of trials evaluating the data obtained is, of Penjas81.33 % (good), the learning I 93.33 % (very good) , the learning II 89.33 % (good), a small group of trial90,87 % (very good), and field test 92.28 % (very good).